2022
DOI: 10.3390/ijms231710077
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal Guidance Molecules in Bone Remodeling and Orthodontic Tooth Movement

Abstract: During orthodontic tooth movement, mechanically induced remodeling occurs in the alveolar bone due to the action of orthodontic forces. The number of factors identified to be involved in mechanically induced bone remodeling is growing steadily. With the uncovering of the functions of neuronal guidance molecules (NGMs) for skeletal development as well as for bone homeostasis, NGMs are now also among the potentially significant factors for the regulation of bone remodeling during orthodontic tooth movement. This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 113 publications
0
2
0
Order By: Relevance
“…1,2 Research has shown that the tension and static pressure generated during the orthodontic process increase bone formation on the tension side and bone absorption on the pressure side. 3,4 Periodontal ligament stem cells (PDLSCs) are mesenchymal stem cell/progenitor cells with multipotent differentiation and self-renewal ability in the periodontal ligament. 5,6 PDLSCs express surface markers related to mesenchymal stem cells and specific biomarkers related to osteogenesis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1,2 Research has shown that the tension and static pressure generated during the orthodontic process increase bone formation on the tension side and bone absorption on the pressure side. 3,4 Periodontal ligament stem cells (PDLSCs) are mesenchymal stem cell/progenitor cells with multipotent differentiation and self-renewal ability in the periodontal ligament. 5,6 PDLSCs express surface markers related to mesenchymal stem cells and specific biomarkers related to osteogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…Orthodontic tooth movement is the spatial displacement of teeth caused by the remodelling of the periodontal ligament and alveolar bone through the transfer of tensile force and static pressure to the alveolar bone from the periodontal ligament when a mechanical stimulus force is applied to the teeth 1,2 . Research has shown that the tension and static pressure generated during the orthodontic process increase bone formation on the tension side and bone absorption on the pressure side 3,4 . Periodontal ligament stem cells (PDLSCs) are mesenchymal stem cell/progenitor cells with multipotent differentiation and self‐renewal ability in the periodontal ligament 5,6 .…”
Section: Introductionmentioning
confidence: 99%